A kalathiskos as an offer: a foundation rite in Jazzo Fornasiello (Gravina in Puglia, BA)? (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The data connected with the “Casa dei Dolii” at Jazzo Fornasiello (Gravina in Puglia, BA) shed new light on ritual practices performed by the Peuketians. As a matter of fact, the construction of the stone building known as room A was preceded by a series of actions, probably to be referred to a foundation rite, concluded with the intentional shredding of the tools used during the ritual. The presence of objects related to the mundus muliebris, such as a banded kalathiskos and a loom weight, suggests that the female sphere played an active role in the management of the sacra.
Keywords: Jazzo Fornasiello; Peucezia; foundation rite; kalathiskos; mundus muliebris